2018
DOI: 10.1002/hed.25427
|View full text |Cite
|
Sign up to set email alerts
|

Virtual evaluation of selected cervical lymph nodes with three‐dimensional ultrasound in thyroid cancer patients after thyroidectomy

Abstract: Background We evaluated the usefulness of three‐dimensional (3D) ultrasound of cervical lymph nodes (LN), when two‐dimensional (2D) ultrasound evaluation is not sufficient to clearly evaluate lymph node characteristics, in thyroid cancer patients being followed after thyroidectomy. Methods Two readers retrospectively analyzed 2D and 3D images of 147 LNs; LNs were categorized as normal, reactive, suspicious, or indeterminate, and confidence level was rated. Results were compared to cytological/clinical data. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…To fully make use of this ratio, 3D‐US may be a useful tool. For hemi‐thyroidectomies Frank et al found use for 3D‐US in differentiating neck lymph nodes after surgery, improving specificity from roughly 0.74–0.9 and increasing the confidence of the readers in their diagnosis 136 . In conclusion, we believe that the use of advanced analysis such as CEUS, shear‐wave elastography and 3D‐US may aid the clinician in identifying vital versus non‐vital tissue and the other diagnostic characteristics mentioned in the various RSS's and as such should be subject of further research.…”
Section: Follow‐upmentioning
confidence: 99%
“…To fully make use of this ratio, 3D‐US may be a useful tool. For hemi‐thyroidectomies Frank et al found use for 3D‐US in differentiating neck lymph nodes after surgery, improving specificity from roughly 0.74–0.9 and increasing the confidence of the readers in their diagnosis 136 . In conclusion, we believe that the use of advanced analysis such as CEUS, shear‐wave elastography and 3D‐US may aid the clinician in identifying vital versus non‐vital tissue and the other diagnostic characteristics mentioned in the various RSS's and as such should be subject of further research.…”
Section: Follow‐upmentioning
confidence: 99%